# Complete the table for the function h(x)=√x-2 X, 0, 1, 4, 9 Y

### 2 Answers | Add Yours

Given `h(x)=sqrt(x)-2` :

`x=0 ==> h(0)=sqrt(0)-2=-2`

`x=1 ==> h(1)=sqrt(1)-2=-1`

`x=4 ==> h(4)=sqrt(4)-2=0`

`x=9 ==>h(9)=sqrt(9)-2=1`

Now y=h(x) so we have:

x h(x) y

-----------

0 -2 -2

1 -1 -1

4 0 0

9 1 1

Set up a x/y table, placing the given x-values as your inputs. Plug each x-value into the radical expression and simplify completely for the output, your y.

x h(x) y

0 sqrt (0) - 2 -2

1 sqrt (1) - 2 -1

4 sqrt (4) - 2 0

9 sqrt (9) - 2 1